Assessment of the Nexus Between Environmental Degradation, Economic Growth, and Population Growth : A Panel Data Analysis - Babu, Swati Sinha (Arthshastra Indian Journal of Economics & Research, 2025)
Purpose : The paper assessed the nexus between population growth and economic growth on forest area and methane (CH4) emission for 11 selected Asian countries from 1990 to 2021. Methodology : We employed panel data regression techniques, i.e., pooled ordinary least squares (OLS), fixed effects model (FEM), and random effects model (REM) for analytical purposes. Further, to check appropriateness between OLS and FE /FE and RE models, we utilized the redundant FE test/Hausman specification test. Findings : The results from REM confirmed the environmental Kuznets curve (EKC)-type relationship between economic growth and forest area. Again, agricultural land expansion, crop production, livestock production, and population growth had a significantly negative impact on forest area, and a 1% increase in them led to a decline in forest area by 0.45%, 0.21%, 0.17%, and 0.016%, respectively. In the case of methane emission, the results failed to confirm the EKC hypothesis. Surprisingly, population growth was found to exert a significantly negative impact on methane emission, and methane emission declined by 0.05% for every 1% increase in it. Practical Implications : It was suggested that to arrest environmental degradation, adequate measures should be adopted, focusing on sustainable intensification of agricultural production, improving livestock and grazing management, and removing trade barriers for foreign investments in cleaner technologies. Originality : Unlike previous studies that have primarily used CO2 emissions as an indicator of environmental degradation, we have used methane emissions and forest area. Moreover, our study is based on those Asian countries that have been seriously affected by climatic change in the past 20 years.